Photoluminescent lead(II) coordination polymers stabilised by bifunctional organoarsonate ligands - SCHMITT, WOLFGANG; SCHMITT, WOLFGANG (My University, 2015)
Four lead(II) coordination polymers were isolated under hydro(solvo)thermal conditions. The applied synthetic methodology takes advantage of the coordination behaviour of a new bifunctional organoarsonate ligand, 4-(1, 2, 4-triazol-4-yl)phenylarsonic acid (H2TPAA) and involves the variation of lead(II) reactants, metal/ligand mole ratios, and solvents. The constitutional composition of the four lead(II) coordination polymers can be formulated as [Pb2(TPAA)(HTPAA)(NO3)]centerdot6H2O (1), [Pb2(TPAA)(HTPAA)2]centerdotDMFcenterdot0.5H2O (DMF = N, N-Dimethylformamide) (2), [Pb2Cl2(TPAA)H2O] (3), and [Pb3Cl(TPAA)(HTPAA)2H2O]Cl (4). The compounds were characterized by single-crystal and powder x-ray diffraction techniques, thermogravimetric analyses, infra-red spectroscopy, and elemental analyses. Single-crystal x-ray diffraction reveals that 1 and 2 represent two-dimensional (2D) layered structures whilst 3 and 4 form three-dimensional (3D) frameworks. The structures of 1, 2, and 4 contain one-dimensional (1D) {PbII/AsO3} substructures, while 3 is composed of 2D {PbII/AsO3} arrays. Besides their interesting topologies, 1–4 all exhibit photoluminescence properties in the solid state at room temperature.
PUBLISHED
Export Date: 22 August 2015
Keywords: bifunctional organoarsonate ligand, 4-(1, 2, 4-triazol-4-yl)phenylarsonic acid (H2TPAA); bifunctional organoarsonate ligand, 4-(1, 2, 4-triazol-4-yl)phenylarsonic acid (H2TPAA)